Impact of drought periods on hydroelectric production in Portugal: A Study from 2015 to 2017 - Sousa, José (2021)
The production of hydroelectric power is strongly affected due to periods of drought. In Portugal there are about forty-nine hydroelectric plants with installed capacity of more than 10MW. In the year 2017 the generation of electricity in Portugal was 54.52 TWh, of which about 14% was hydroelectric production reflecting a year below normal in hydroelectric power production. This article discusses the impact of drought periods on hydroelectric power production in Portugal, which address the importance of hydroelectric production in Portugal. Among the factors influencing the production of hydroelectric power, a method is presented for analysis of a dry month through the monthly precipitation indicators, energy production by monthly technology and energy price. These indicators were presented and analyzed in three case studies presented in this article. A solution is also presented to reduce the impact of drought periods on Hydro production.